Analisis Kebutuhan Pengembangan E-Modul Sejarah Indonesia untuk Meningkatkan Keterampilan Berpikir Kausalitas Peserta Didik - Ismi, Amanda; Afriani, Rini (Jurusan Sejarah FIS UNP, 2026)
This study aims to analyze the needs for developing an e-module designed to enhance students’ causal thinking skills in Indonesian history learning. The research employed a descriptive qualitative approach as the initial stage (Analyze) of the ADDIE development model. The subjects consisted of history teachers and 11th-grade students at MAN 3 Kota Padang. Data were collected through observation, interviews, and documentation to identify learning needs, challenges encountered, and the availability of supporting facilities. The findings revealed that history learning at MAN 3 Kota Padang remains conventional and teacher-centered, relying on unattractive materials that do not effectively stimulate higher-order thinking skills. Most students demonstrated low causal thinking abilities, particularly in understanding cause-and-effect relationships among historical events. Based on these findings, it is necessary to develop an interactive, contextual, and easily accessible digital e-module to support more meaningful history learning and improve students’ causal thinking skills.